A comprehensive review on the environmental impacts of diesel/biodiesel additives. (15th October 2018) - Hosseinzadeh-Bandbafha, Homa; Tabatabaei, Meisam; Aghbashlo, Mortaza; Khanali, Majid; Demirbas, Ayhan
Highlights: Effects of various diesel/biodiesel additives comprehensively reviewed & discussed. Effect of engine operating factors on regulated and nonregulated emissions reviewed. Research works related to life cycle assessment of biodiesel was reviewed. Abstract: Biodiesel, in its neat or blended form with petrodiesel, is widely accepted alternative fuel for diesel engines. Although biodiesel is presumably associated with lower CO2, HC, and PMs emissions, it suffers from its own drawbacks including higher viscosity, lower volatility, lower heating value, and higher NOx emissions. In order to address these shortcomings and to meet stringent emission norms, diesel/biodiesel additives have attracted more attention recently owing to their ability to improve engine performance and mitigate hazardous emissions. While discrete emissions analysis could provide useful information on environmental impacts associated with various fuel additives, decision-making on such basis would be very difficult or even impossible since different fuel additives may have different positive/negative effects on pollutants generated during combustion process. This issue becomes even more serious in multi-objective optimization studies due to the fact that considering all emission indices for finding a global optimal point would be very complex as a result of conflicting objectives. Moreover, exhaust gas emission analysis does not consider environmental impacts caused in fuel production process. Discrete emissions analysis also lacks weighting in decision-making procedure since the level and degree of harmfulness of pollutants may not be comparable. Life cycle assessment (LCA) has been recognized as a valuable tool to address these challenges through systematical evaluation of potential environmental impacts of fuel additives. Accordingly, this paper was aimed at comprehensively reviewing and mechanistically discussing the effects of various diesel/biodiesel additives including metal-based, oxygenated, antioxidant, cold flow improver, lubricity improver, and cetane number improver additives as well as engine operating parameters like engine load, engine speed, EGR, and injection timing on both regulated and non-regulated emissions. Moreover, the environmental impacts of various diesel/biodiesel additives by incorporating an LCA approach was also critically discussed.